Sistem Perkreditan di Lombok Tahun 1895-1941: Credit System in Lombok 1895-1941 - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2003)
The purpose of this research is to know credit system in Lombok in period of 1895-1941. Although to flatten the concern West credit recognizable by colonialism of Dutch but to know too credit system before Lombok below authority colonial Dutch. In year 1852 to go on lend or borrow and traditional debt to go on this people village in Lombok, this creates and to regulated by government empire system. The kepeng bolong in use transaction it. The traditional debt based in trust and agreed between borrower and receiver lend. The transaction debt to be in model pangeling-eling or katrangan with transaction time or dated, the stamp legalization by official empire. The Colony government to make capability in people credit with to founded Volksccredietbank in Mataram. The found Volkscredietbank to purpose has been trained people for to learn the saving and lend in Bank. Along the Volkscredietbank government to be monetary capability with to take kepeng bolong (Chinese coins) and to alternated by gulden money, ringgit and sen. Thus money to use transaction and to pay in economic transaction. The Volkscredietbank an West institute credited has not to realize unfolding in the direct best prospect, between caused by economy depreciation, in used not legally borrow or harvest failure so that borrower not capable to back borrow.